Controlled On-Chip Single-Photon Transfer Using Photonic Crystal Coupled-Cavity Waveguides. (4th November 2010) - Seigneur, Hubert Pascal; Weed, Matthew; Leuenberger, Michael Niklaus; Schoenfeld, Winston Vaughan
Abstract : To the end of realizing a quantum network on-chip, single photons must be guided consistently to their proper destination both on demand and without alteration to the information they carry. Coupled cavity waveguides are anticipated to play a significant role in this regard for two important reasons. First, these structures can easily be included within fully quantum-mechanical models using the phenomenological description of the tight-binding Hamiltonian, which is simply written down in the basis of creation and annihilation operators that move photons from one quasimode to another. This allows for a deeper understanding of the underlying physics and the identification and characterization of features that are truly critical to the behavior of the quantum network using only a few parameters. Second, their unique dispersive properties together with the careful engineering of the dynamic coupling between nearest neighbor cavities provide the necessary control for high-efficiency single-photon on-chip transfer. In this publication, we report transfer efficiencies in the upwards of 93% with respect to a fully quantum-mechanical approach and unprecedented 77% in terms of transferring the energy density contained in a classical quasibound mode from one cavity to another.